Sustainable Engineering: Utilisation of Biomedical Waste Ash for Untapped Potential in Soil Stabilisation - Pooja Somadas; Purushotham G Sarvade (International Journal of Sustainable Engineering)
The disposal of biomedical waste (BMW) ash presents a growing environmental concern due to its potential to contaminate ecosystems and causes health hazards. This study explores an innovative solution by utilising BMW ash as a sustainable stabiliser to enhance the geotechnical properties of a soft soil, which exhibits low strength and high plasticity characteristics. Through the application of the Taguchi method, the influence of BMW ash concentration and curing period on the soil properties such as compaction, pH, electrical conductivity, and unconfined compressive strength (UCS) were evaluated. The experimental results show that adding BMW ash significantly reduces soil plasticity and increases UCS, achieving a strength gain of more than 180 kPa within 14 days. The optimal combination was determined to be 20% BMW ash with a 14-day curing period. Analysis of variance (ANOVA) revealed that the curing time is the dominant factor, contributing 90.86% to early strength development. Microstructural analysis using SEM and EDX further reveals the formation of ettringite, which promotes early strength gain. This research demonstrates the dual benefits of BMW ash in mitigating environmental waste while improving soil performance, offering a viable solution for both waste management and soil stabilisation challenges.